Disruption of temporally extended self-memory system following traumatic brain injury. (May 2015) - Coste, Cécile; Navarro, Béatrice; Vallat-Azouvi, Claire; Brami, Marie; Azouvi, Philippe; Piolino, Pascale
Abstract: We investigated for the first time the episodic/semantic distinction in remembering the past and imagining the future in traumatic brain injury (TBI), and explored cognitive mechanisms that may underlie their deficits. Fifteen severe TBI patients and 15 control participants performed a battery of neuropsychological tests and a set of verbal fluency tasks designed to assess semantic (personality traits knowledge and general events), and episodic (specific events and details) facets of self-representations according to three time periods (remote/retrograde past, recent/anterograde past, future). Compared to controls, TBI patients showed deficits in both semantic and episodic self-representations, regardless of the time period, and controlling for basic cognitive functions. By contrast, a subjective evaluation of self-concept measuring the degree of certitude and the valence of self did not differ between patients and controls. The deficits were mainly predicted by altered executive function (i.e., updating) for past periods, as well as by general semantic and feature binding in working memory for the future period, independently of the injury characteristics. For controls, only episodic self-representation for each time period was mediated by executive or working memory functions, while semantic self-representation was mediated by the certitude of the self. This study highlights the dual role of semantic and episodic representations in temporally extended self, and shows the global disruption of self-representations across extended time in severe TBI. This encourages the extension of past and future thinking research to TBI populations to provide important insights into the nature and origin of these deficits and their role in recovery and to suggest future lines of research on rehabilitation procedures. Highlights: We examine self-memory system extended in time in patients following TBI. We assess semantic/episodic self-representations across past and future periods. All self-representations are reduced across past and future periods in TBI. These deficits are linked to executive function in retrieving past periods. Future self-representations are mediated by semantic/feature binding functions